BIROKRASI PEMERINTAHAN DALAM PENYELENGGARAAN PELAYANAN PUBLIK - Kiki Endah (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
Bureaucracy is an institution that has great ability to move the organization. Because the bureaucracy is formally organized to carry out rational actions in an organization. Bureaucracy is the order of an organization in which it has a structure, division of tasks, and a hierarchy. Where the bureaucracy is run by many people with clear rules, fixed procedures, and led by someone with the inherent authority in giving orders to be carried out by his subordinates solely for the benefit of the community. Government bureaucracy as an important tool in a country is inevitable because its presence is needed by the wider community, so that where there is a state there must be a bureaucracy. The community, of course, asks the government for the right to service related needs that cannot be provided by private organizations. However, in the end, the people's mindset was trapped in the reality of the blurring of the services provided, such as the slow completion of administration, long and convoluted procedures, ineffective and efficient, and seemed indifferent, and not friendly and so on. The needs that cannot be met by the private sector cause the community to be forced to deal with bureaucratic officers of rigid government organizations and have monopoly rights that can solve public affairs. The government as a public servant should have a big obligation and responsibility to provide the best service for the community to be fair, transparent and responsible, all of which are to provide satisfaction to the community